Resource allocation algorithm for energy efficiency optimization of multicarrier NOMA downlink system - Peng, Yue; Yang, Jie; Zhao, Bing; Yang, Shiyu (SPIE, 2022)
Aiming at the problem of efficient allocation of radio resources for massive users in Non-Orthogonal Multiple Access (NOMA) systems, a user-subchannel bilateral dynamic matching algorithm is proposed. First, a joint user-subchannel and power allocation optimization problem for multi-carrier NOMA systems is established with the target of maximizing system energy efficiency. The user-subchannel is modeled as a bilateral many-to-many matching game, the GaleShapley matching algorithm is introduced, and an efficient two-sided matching algorithm is proposed to achieve the dynamic and stable matching of the user-subchannel. Then, on this basis, the power allocation problem is allocated to the power resources through the convex difference (DC) planning algorithm. From the simulation results. Compared with the traditional matching algorithm, equal power allocation algorithm and orthogonal frequency division multiple access scheme, the proposed algorithm can improve the system energy efficiency and converge faster.